Global, Regional, and National Levels of Fruit and Vegetable Consumption from the ROUND (WoRld Map of COnsUmption of Fruit and Vegetables and Nutrient Deficits) Project (P18-067-19) - Gregori, Dario (Curr Dev Nutr, 2019)
OBJECTIVES: Low fruit and vegetable consumption is one of the most important modifiable risk factors for obesity and chronic diseases, especially cardiovascular diseases and some types of cancer. The aim of the ROUND (WoRld Map of COnsUmption of Fruit and Vegetables and Nutrient Deficits) Project is to evaluate global consumption of fruit and vegetables and to characterize the distribution of related nutrient deficiencies. METHODS: Data relating to adult consumers from dietary surveys worldwide were identified, obtained, and assessed. Analyses were performed using Bayesian hierarchical models. RESULTS: Data from different worldwide surveys were included in the analysis. Results show considerably variation between countries, even for those of middle-high income. For example in 2007, the mean per capita daily consumption of fruit (including fruit juice) and vegetables (and total) were: USA 325 g and 505 g (830 g, Census data); Germany 624 g and 106 g (730 g); Finland 429 g and 130 g (559 g); Netherlands 345 g and 133 g (478 g), and France 238 g and 145 g (382 g); (EFSA data). In 2012, an estimated 6.7 million deaths worldwide were attributable to a low intake of fruit and vegetables in both high and low-middle income countries. CONCLUSIONS: ROUND analysis of data on adult fruit and vegetable consumption identifies diversity across nations, which can inform policies and assist in setting priorities for improving global health. FUNDING SOURCES: ZETA RESEARCH S.r.l.